Corporate social responsibility in agribusiness: dimensions affecting performance - Martínez-Caro, Eva (2012)
Corporate Social Responsibility (hereinafter CSR) may explain the achievement of competitive advan- tages. CSR aims to minimize the negative effects that several aspects of the organization cause in the environment. With the development of a CSR, businesses, in addition to carrying out “good prac- tices” in their activities, could be considered socially responsible agents, improving its image, status and corporate reputation. The relationship between CSR and financial performance has been the subject of controversial discussion for years. This research aims to provide new insights into this debate consi- dering as main objective to analyze how it influences the development of culture in terms of CSR and the contribution to the realization of the strategic dimensions or measures of CSR, on business per- formance. An empirical study with a sample of 226 companies in the agribusiness sector was developed. The results indicate that both the strategic dimen- sions that refer to the social values as CSR measures involving interest groups, influence business results.